The R/Evolution of South Africa's Public Education System Post-1994 in an Era of Privatisation - Chetty, Pagiel Joshua (School of Education, 2024)
The purpose of this study is to investigate how the concept of education as a public good in South Africa has been affected by privatisation since 1994. This study locates itself within a human rights framework, which is premised upon South Africa's (seemingly progressive) Constitution of 1996 and seeks to investigate the potential shift of education as a public good (that truly benefits the public) towards a more market-based and neoliberal approach to education provision. In this regard, I analyse the annual South African education budget vote speeches presented in the South African Parliament by successive post-apartheid Ministers of Education from 1994 to 2021. As its core focus, this study theorises that the notion of education as a public good has shifted and changed in meaning since 1994. I investigate this by tracking its perceived change in meanings using a qualitative research design known as the Narrative Policy Framework, which I leverage using a Thematic Analysis approach. This approach is used as a data reduction and analysis strategy. This study argues that the rearticulation of public education under the broad rubric of neoliberal thought has fundamentally impacted the concept of education as a public good and education as a fundamental human right in South Africa in the post-apartheid era. Furthermore, despite the goal of making education universally available, the increasing encroachment of ‘the market' in public education provision consolidates and creates new forms of inequalities, thereby enlarging the general inequality gap.